(NtWORI W DWOH TOMAH (B/s (Nt(B. 2 /s - (NwOW^OK(B, (NmARKO (B(1833-1907)s; (Nb)QÆLQWSXKOÇ(B, (No(B.,s)E; (NwOW^OK(B, (NmARKOs 1833-1907 ((NkI)QÇW (B:s)E (NdN)QÆPRO(B,s)E, 1983)
(NdO DRUGOGO TOMU WW)QÆJ[LI POWÆSTX (B"(NmARUSQ(B", (NOPOWÆDANNQ(B, (NKAZKI(B, (NNARISI(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKA LÆTERATURAs)E -- (NtWORIs